2014
DOI: 10.2220/biomedres.35.381
|View full text |Cite
|
Sign up to set email alerts
|

Fasudil, a Rho kinase inhibitor, suppresses tumor growth by inducing CXCL14/BRAK in head and neck squamous cell carcinoma

Abstract: CXCL14/BRAK (BRAK) is a secreted chemokine with anti-tumor activity, and its expression is suppressed in tumor cells. We previously reported the anti-tumor activity of BRAK in cell lines of head and neck squamous cell carcinoma (HNSCC) and the suppression of BRAK secretion in these cells. BRAK secretion in fibrosarcoma cells is restored by Fasudil, which is a Rho-kinase (ROCK) inhibitor. In this study, we examined the anti-tumor effect of BRAK by evaluating its gene expression and protein secretion in HNSCC ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…CXCL14 may also induce tumor suppression in other cancers beyond HPV-positive cancers, as CXCL14 expression is downregulated in several cancers including renal and gastric cancers [18,19]. Indeed, restoration of CXCL14 expression triggers tumor suppression in lung and colorectal cancers, as well as HNC [44,48,49]. In addition, CXCL14 could be used to treat HPV-positive premalignant lesions for cancer prevention.…”
Section: Discussionmentioning
confidence: 99%
“…CXCL14 may also induce tumor suppression in other cancers beyond HPV-positive cancers, as CXCL14 expression is downregulated in several cancers including renal and gastric cancers [18,19]. Indeed, restoration of CXCL14 expression triggers tumor suppression in lung and colorectal cancers, as well as HNC [44,48,49]. In addition, CXCL14 could be used to treat HPV-positive premalignant lesions for cancer prevention.…”
Section: Discussionmentioning
confidence: 99%
“…In head and neck squamous cell carcinoma (HNSCC), CXCL14 expression and secretion and its anti-tumor effect is negatively regulated by RhoA/ROCK pathway. Therefore Fasudil, ROCK-specific inhibitor can stimulate CXCL14 expression [ 37 ]. In clear cell renal cell carcinoma, S100A6 (Calcyclin), as an oncogenic protein, negatively regulates CXCL14 expression, and knockdown of S100A6 promotes CXCL14-mediated apoptosis and promotes tumour progression [ 38 ].…”
Section: Regulation Of Cxcl14 Expression At Transcript and Protein Lementioning
confidence: 99%
“…Low CXCL2, 3, and 12 mRNA levels predicted high RFS, suggesting that they play important regulatory roles in promoting tumor recurrence. Although few studies have investigated CXCL14, high CXCL14 expression has been found to suppress tumor growth in HNSC [ 41 ]. We found that CXCL14 is associated with tumor stage, OS, and RFS, suggesting that it could be an important target for treating HNSC.…”
Section: Discussionmentioning
confidence: 99%